Differentially Regulated Transcription Factors and ABC Transporters in a Mitochondrial Dynamics Mutant Can Alter Azole Susceptibility of Aspergillus fumigatus - Sturm, Laura; Geißel, Bernadette; Martin, Ronny; Wagener, Johannes (Frontiers in Microbiology, 2020)
Azole resistance of the fungal pathogen Aspergillus fumigatus is an emerging problem. To identify novel mechanisms that could mediate azole resistance in A. fumigatus, we analyzed the transcriptome of a mitochondrial fission/fusion mutant that exhibits increased azole tolerance. Approximately 12 % of the annotated genes are differentially regulated in this strain. This comprises upregulation of Cyp51A, the azole target structure, upregulation of ATP-binding cassette (ABC) superfamily and major facilitator superfamily (MFS) transporters and differential regulation of transcription factors. To study their impact on azole tolerance, conditional mutants were constructed of seven ABC transporters and 17 transcription factors. Under repressed conditions, growth rates and azole susceptibility of the mutants were similar to wild type. Under induced conditions, several transcription factor mutants showed growth phenotypes. In addition, four ABC transporter mutants and seven transcription factor mutants exhibited altered azole susceptibility. However, deletion of individual identified ABC transporters and transcription factors did not affect the increased azole tolerance of the fission/fusion mutant. Our results revealed the ability of multiple ABC transporters and transcription factors to modulate the azole susceptibility of A. fumigatus and support a model where mitochondrial dysfunctions trigger a drug resistance network that mediates azole tolerance of this mold.